The Relationship between Extensioners Assistance and Produktivity in The Muaro Farming Group Diateh lake Solok District - Deni, Rahma; Irmawita, Irmawita (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2024)
This study aims 1) to find out the form of the implementation of extension assistance to the Muaro Danau farmer groups in Ateh, Solok Regency. 2) To find out the obstacles in the implementation of extension assistance to the Muaro Danau farmer group at the Solok Regency. 3) To find out the relationship between extension assistance and the productivity of the Muaro Danau farming business in Ateh, Solok Regency. This research was conducted in Jorong Usak Nagari Alahan Panjang, Lembah Gumanti District. The research method was carried out through correlational quantitative research using a questionnaire. The research informants were the Solok District Agriculture Office, extension assistants, and Farmer Groups. Data collection techniques in this study used a questionnaire. The data analysis technique uses the Spearman Rho formula. The results showed that the relationship between extension assistance and productivity in the Muaro Danau Above Farmer Group in Solok Regency was carried out using various methods. However, in its implementation there are still several obstacles, especially the problem of time and attendance of participants. Keywords: Extension Extension Assistance, Productivity, Farmer Groups